Pengaruh Penambahan Monosodium Fosfat pada Pembuatan Processed Cheese dengan Koagulan Sari Nanas terhadap Kadar Air, Rendemen, dan Akseptabilitas - Ida Ayu Marintan Raisanti; Wendry Setiyadi Putranto; Deden Zamzam Badruzzaman (Jurnal Teknologi Hasil Peternakan, 2022)
Processed cheese is a natural cheese that has undergone further processing to produce a more homogeneous texture. Bromelain enzyme derived from pineapple fruit which was used as a coagulant. Emulsifier in the form of monosodium phosphate (NaH2PO4) was used as an emulsifier. This study was aimed to determine the effect of the NaH2PO4 addition on moisture content, yield, and acceptability of processed cheese with pineapple juice coagulant. This research was conducted by experimental method using a completely randomized design with a significance level of 5% for 3 treatment concentrations (P1=2%, P2-3%, and P3=4%). Each treatment was repeated 6 times. If there was a difference, Duncan’s further test is carried out. Acceptability data was tested using Kruskal-Wallis, if there was a difference, the Mann-Whitney further test was carried out. The results showed that the use of NaH2PO4 with concentration of P1 (2%), P2 (3%) and P3 (4%) had no effect on moisture content and yield. The best acceptability value was found in P2 (3%) with a numerical scale for the best taste, namely 3.67 (slightly like-like), color 3.73 (slightly like-like), aroma 4.27 (like-like very much), texture 3.60 (slightly like-like), and the total acceptance is 3.53 (slightly like-like).